Determinants of morphologic cardiac adaptation in elite athletes: the role of athletic training and constitutional factors - Pelliccia, A. (International Journal of Sports Medicine, 1996)
Endurance sports lead to physiological enlargement of the heart and to an increase in wall thickness, depending on the kind of endurance sport and on the intensity and extent of training. The adaptation of the heart is modified by several factors. Antropometric parameters (height, body composition), sex and genetic traits are potential mechanism.